Participatory Auditing: Lessons from Philippines and South Korea and its Implementation in The SAI of Indonesia - Aziliya, Dara; Sampurna, Agung Firman (Syntax Literate, 2024)
Supreme Audit Institutions (SAI) are crucial for promoting accountability and transparency, especially in countries such as Indonesia, where corruption and government fraud are widespread. These institutions help the public monitor the government and ensure that public funds are used effectively and efficiently. Achieving good governance requires close collaboration between people and SAI. This study emphasizes the importance of people's participation in Indonesia SAI (Badan Pemeriksa Keuangan/BPK) to identify public issues for auditing purposes. Every year, the BPK conducts over 500 audits, including financial, performance, and auditing with special purposes. BPK produces over 9,000 findings that the government needs to follow. This paper highlights the success stories of participation audits in the Philippines and South Korea, and how Indonesian SAI can learn from both. By working together with the public, audit reports can benefit stakeholders and contribute to better governance.